ANALISIS SALURAN PEMASARAN KERIPIK GADUNG (Dioscorea hispida L.) PADA USAHA HOME INDUSTRY DUA PUTRA JAYA DI KABUPATEN JOMBANG - Muhammad Amir Ma'sum; Umi Kulsum Nur Qurmariah (Program Studi Agribisnis, 2021)
This study aims to determine the form of marketing channels, marketing margins, share of the price received by producers and marketing efficiency of gadung chips in the